People and Blackbuck: Current Management Challenges and Opportunities - Bhatta, Shiv Raj (The Initiation, 2010)
Blackbuck is one of the most magnificent animals living in close proximity to human settlement. The last surviving population of blackbuck in Nepal is found at Khairapur of Bardia District in west Nepal. The problem of land and management responsibility has been a issue for more than last 3 decade. The current issues of the management are related to: Policy, legal and institutional, habitat management, database and research and the livelihood of the neighboring communities has been briefly presented. A draft 5 year action plan has been prepared by the Department to address these issues and ensure the long-term survival of the last remaining population of blackbuck in Nepal. This new model of community participation proposed for conservation and management of the area and this protected species can be taken as an opportunity for conservation. Though the area has been encroached by some illegal settlers, long-term survival of this endangered species in the middle of village without community participation is impossible. Key Words: Blackbuck, Protected mammal, Habitat management, Crop damage, Conservation committee. DOI: 10.3126/init.v2i1.2514 The Initiation Vol.2(1) pp17-21